Genomic Regions Associated With Salinity Stress Tolerance in Tropical Maize (Zea Mays L.) - Zaidi, Pervez H.; Shahid, Mohammed; Seetharam, Kaliyamoorthy; Vinayan, Madhumal Thayil (Frontiers in Plant Science, 2022)
Maize, being a widely cultivated crop globally in diverse climatic conditions and soil types, is often exposed to an array of biotic and abiotic stresses. In recent past, significant losses have been reported on crop growth and economic yields of maize crop in many parts of tropics due to salinity stress. Breeding strategies integrated with molecular breeding ap-proach might quicken the process of identifying and developing salinity tolerant maize cul-tivars. In the present study, an association mapping panel consisting of 305 diverse tropical maize inbred lines were phenotyped at the managed stress phenotyping facility at Interna-tional Center for Biosaline Agriculture (ICBA), Dubai, United Arab Emirates (UAE). A wide diversity was observed in the panel under soil salinity stress for key phenotypic traits viz., grain yield, days to anthesis, anthesis-silking interval, plant height, cob length, cob girth and kernel number. The panel was genotyped to generate 955,690 SNPs using Illumina Hi-seq 2000/2500. Total SNPs were filtered to 213,043 SNPs at a call rate of 0.85 and minor allele frequency of 0.05 for association analysis. A total of 311 highly significant (P=<10-5) marker-trait associations were identified for the seven phenotypic traits. Phenotypic vari-ance for the maker-trait associations ranged from 9.4 to 5.2%. Among the significant mak-er-trait associations, a total of 236 associations were found within 151 unique putative gene expression regions Among them, 12 associations were found in the gene models with stress related biological functions, which are discussed in this paper.